Enhancing Public Service Delivery Through Digital Green Leadership: A Systematic Review Of Smart Village Waste Management - Uli Nuha; Suparman Suparman; M. Hatta; Jamaluddin Ahmad; Muhammad Rais Rahmad Razak; Erfina Erfina; Ahmad Mustanir; Sandi Lubis (Lembaga Bale Literasi, 2026)
This study aims to analyze the development of public service delivery research within the context of digital green leadership in smart village-based waste management. The research employs a qualitative approach using a Systematic Literature Review (SLR) of 700 scientific articles indexed in the Scopus database, analyzed through content analysis and bibliometric mapping using VOSviewer. The findings reveal a significant increase in multidisciplinary research trends, dominated by social sciences, environmental studies and digital technology. Keyword network analysis identifies three major clusters: empirical, conceptual and implementation-based approaches, which are highly interconnected. The results indicate that improving public service delivery is strongly influenced by the integration of digital governance, green leadership, smart village and waste management policy. Furthermore, digital green leadership emerges as a key driver in promoting efficient, participatory and sustainable public services. This study concludes that an integrative approach combining technology, leadership and policy is essential for advancing future public service delivery systems.